Everolimus plus anastrozole for female adnexal tumor of probable Wolffian origin (FATWO) with STK11 mutation - Maria de Pilar Estevez-Diz; Renata Colombo Bonadio; Filomena Marino Carvalho; Jesus Paula Carvalho (Elsevier, 2021)
Female adnexal tumor of probable Wolffian origin (FATWO) are a rare type of cancer that originates from Wolffian duct remnants. Due to its rarity, no standard systemic treatment is established for cases of recurrent or metastatic disease. Previous literature reported the use of platinum-based chemotherapy and c-Kit tyrosine kinase inhibitors for FATWO cases with c-Kit positive expression. Currently, however, the broader availability of next-generation sequencing (NGS) tests allows a better molecular characterization of rare cancer such as FATWO and a possibility for the use of personalized, targeted therapy. Previous case series that performed NGS for FATWO patients described the presence of STK11 mutations in a considerable number of cases, representing a potential target in this population. To our knowledge, we describe here the first case report of a patient with FATWO and STK11 mutation exhibiting a considerable and durable response after treatment with an mTOR inhibitor plus endocrine therapy.